Isolation and identification of Wickerhamiella tropicalis from blood culture by MALDI-MS - Takei, Satomi; Teramoto, Kanae; Fujimura, Junya; Fujiwara, Megumi; Suzuki, Mai; Fukui, Yukiko; Sekiguchi, Yuji; Kawakami, Takaaki; Chonan, Masayoshi; Wakita, Mitsuru; Horiuchi, Yuki; Miida, Takashi; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
The infections of non-Candida albicans species have significantly increased in recent years. Early use of antifungal treatment is recommended to reduce the mortality, but the selection of antibiotics for non-Candida albicans species is difficult because of the various susceptibilities. The blood stream infection caused by Wickerhamiella species was firstly reported in Qatar in 2006, and then in Greece in 2008, in Qatar in 2010, in the United States in 2017, and in Iran in 2022. PCR and sequencing of the ITS regions combined with the morphology were reliable for the identification of rare fungal species that caused severe infection, but it takes at least 72 h for the identification by morphological observation and sequencing. Therefore, it is important to establish rapid and accurate identification for severe fungal infections. In this study, we newly detected three novel peaks specific for W. tropicalis by MALDI-MS. We demonstrated the potential of MALDI-MS analysis to identify rare fungal species, including Wickerhamiella species, in routine microbiological examinations.